Effect of multiple freeze-thaw cycles on selected biochemical serum components - Gislefoss, Randi E.; Lauritzen, Marianne; Langseth, Hilde; Mørkrid, Lars (Clinical chemistry and laboratory medicine, 2017)
To maintain the best performance a frozen serum sample should be thawed once to prevent repeated freeze-thaw cycles. Archival biobanks often have one tube of a sample available, causing repeated freeze-thaw cycles when the sample is used in multiple research projects. In this study, we investigated potential effects of freeze-thaw cycles on several biochemical components in serum. Serum from 40 fasting donors of both genders, aged 30-60 years, were frozen at -25 °C. Aliquots of the 40 different samples went through 1, 2, 3, 4, 5 and 10 thaws, respectively. They were analyzed after 3 month of storage for 15 serum components including electrolytes and metabolites, proteins and enzymes, lipids, hormones and vitamins. One-way analyses of variance (ANOVA) with repeated measurements and equivalence tests were used to examine differences in component levels. Albumin, aspartate-aminotransferase (ASAT), cholesterol, creatinine, C-reactive protein, glucose, immunoglobulin G, potassium, testosterone, triglycerides, urea and vitamin B12 levels did not show significant difference for pairwise comparisons after 10 repeated thaws. Although albumin, ASAT, bilirubin, potassium, sodium, testosterone and thyroid stimulating hormone (TSH) showed overall statistically significant changes in serum levels, only bilirubin, sodium and TSH were significant for the pairwise comparisons investigated. Clinical significance were shown for albumin, ASAT, bilirubin, sodium and testosterone. Twelve components (albumin, ASAT, cholesterol, creatinine, C-reactive protein, glucose, immunoglobulin G, potassium, testosterone, triglycerides, urea and vitamin B12) were robust to 10 repeated thaws compared to baseline level. Three components (bilirubin, sodium and TSH) showed statistical significant difference for pairwise comparisons, however, TSH was not clinically affected.